Maridos dominadores, esposas (in)subordinadas: as implicações do empoderamento feminino e da masculinidade hegemônica na violência conjugal - Cortez, Mirian Béccheri (2006)
This study investigates how gendering conceptions and practices affect couples conflicts and husband s physical, psychological or sexual violence against his partner. Four couples, which have police report of physical aggression perpetrated by husbands against their wives and an history of this kind of violence, were individually interviewed, based on a two-section instrument: the first part collected participant s socio-demographic data and, the second one, an interview script, aimed to investigate the participants conceptions about man, woman and couple relationship. Data were analyzed by using software Alceste (Analyse Lexicale par Contexte d um Ensemble de Segments de Texte) and Content Analysis. Results demonstrated the agreement between husbands and wives about two relevant points: a) traditional gender conceptions which guide domestic practices and the couple relationship and, b) comprehension that violence episodes result of husbands attempt to control female behaviors they understand as wrong or inadequate. These behaviors have in common the fact they threat the hegemonic model of masculinity and deny, someway, the traditional and naturalized conception of women, as the access to public domain as a result of paid work. Wives detailed the violence contexts, types of aggression (physical, psychological and/or sexual) and physical and emotional injuries. On the other hand, husbands denied occurrences of sexual violence and minimized physical aggressions and their consequences by describing fights as episodes of little or ephemeral implications to their wives and relationships. Results were discussed based on two main concepts, hegemonic masculinity and female empowerment, emphasizing the violent reactions of the interviewed husbands when in confront with their wives signs of autonomy and approaches to male and female prejudices occasioned by man s exclusion from debates about female empowerment.